Qualidade fisiológica de sementes e estabelecimento do consórcio aveia-preta e azevém sob fixação biológica de nitrogênio em sistema de integração lavoura-pecuária - Cunha, Vinícius dos Santos (2014)
In southern Brazil the consortium oat and ryegrass is the most used during the winter period in the crop-livestock system. One of the barriers in this system refers to the waiting period forage when there is shortage of fodder for livestock. The duration of this period should be as short as possible, so that the grazing of animals is anticipated. Alternatively to shorten the forage empty, has the use of the bacterium Azospirillum brasilense, microorganism with potential for nitrogen fixation. Therefore, the study was developed to evaluate the initial performance of the oat and ryegrass under consortium inoculation of the bacteria. The study consisted of two experiments. The first entitled "Influence of chemical treatment and inoculation with Azospirillum brasilense on the physiological quality of seeds of oat and ryegrass", aimed to evaluate the effect of inoculation associated with chemical seed treatment on seed physiological performance of the consortium in 2012 and 2013. The second, entitled "Initial establishment of plants consortium oat and ryegrass under inoculation with Azospirillum brasilense, in integrated crop-livestock system" aimed to evaluate the effect of inoculation on the growth of plants of the consortium in the field. The inoculation showed satisfactory results on some characteristics of species of the consortium, as the accumulation of dry matter in oat seedlings in 2012, and for two years in ryegrass. In the field, inoculation provided greater number of leaves and tillers of both species, while plant height was only stimulated in corn stubble.